Simulated Electronic Health documentation using Integrated Nursing Education System: Nursing students’ perceptions, attitudes and intention to use - Chan, K.G; Saloma, Pawi; Ong, M.F; Goy, Siew Ching; Yanika, Kowitlawakul (2017)
This study aims to examine the nursing students’ perceptions, attitudes, intention to use a simulated, web-application iNES for electronic health documentation and factors influencing their intention to use. Study guided by Technology Acceptance Model hopes to generate insights which would influence the future move of integrating educational, simulated electronic health documentation into the nursing curricular locally. A cross-sectional study design using self-administered questionnaire is adopted. A convenience sampling of 133 undergraduate nursing students in their year 2 to year 4 of study from one of the local public universities were recruited. Students were asked to access the iNES as part of the teaching-learning activities during the semester. Questionnaires were administered to the students at the end of one academic semester. Regression estimates indicate that both attitude toward using and perceived usefulness had significant effect on their intention to use iNES. Together they explained about 39% of the variation, with perceived usefulness displayed a greater extent of influence ((=0.475; p<0.001). Perceived usefulness is statistically significant in its influence on attitude toward using (=0.370, p<0.001). Students’ perceived ease of use did predict a positive significant influence on their perceived usefulness (=0.857, p<0.001). Educators in the faculty would do well to focus on explaining the usefulness of educational web-application to keep students motivated before assigning them to actually access it to practice simulated electronic documentation. Having an application which is user friendly and with adequate access to technological support are important to influence students’ intention to navigate the application for their learning.